2009
DOI: 10.1128/jvi.00672-09
|View full text |Cite
|
Sign up to set email alerts
|

The Linear Plasmid Prophage Vp58.5 of Vibrio parahaemolyticus Is Closely Related to the Integrating Phage VHML and Constitutes a New Incompatibility Group of Telomere Phages

Abstract: Vibrio parahaemolyticus O3:K6 pandemic strains recovered in Chile frequently possess a 42-kb plasmid which is the prophage of a myovirus. We studied the prototype phage VP58.5 and show that it does not integrate into the host cell chromosome but replicates as a linear plasmid (Vp58.5) with covalently closed ends (telomeres). The Vp58.5 replicon coexists with other plasmid prophages (N15, PY54, and ⌽KO2) in the same cell and thus belongs to a new incompatibility group of telomere phages. We determined the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…15 We could not identify any previously characterized phages with ≥ 40% similarity that would belong to the same genus as ϕH111-1. Currently, phages with the most similar proteomes are AcaML1 of Acidithiobacillus caldus (JX507079.1; 28.17% similar) and the "Vhmllikevirus" phages VHML of Vibrio harveyi (NC_004456.1; 28.07% similar) and both [16][17][18][19] Although these phages share subfamily-level similarity, they are very distinct with respect to aspects such as host, gene content, and lifestyle. AcaML1 lysogenizes a thermophilic and acidophilic γ-proteobacterium and has a significantly larger 59 kbp genome with two insertion sequences.…”
Section: Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…15 We could not identify any previously characterized phages with ≥ 40% similarity that would belong to the same genus as ϕH111-1. Currently, phages with the most similar proteomes are AcaML1 of Acidithiobacillus caldus (JX507079.1; 28.17% similar) and the "Vhmllikevirus" phages VHML of Vibrio harveyi (NC_004456.1; 28.07% similar) and both [16][17][18][19] Although these phages share subfamily-level similarity, they are very distinct with respect to aspects such as host, gene content, and lifestyle. AcaML1 lysogenizes a thermophilic and acidophilic γ-proteobacterium and has a significantly larger 59 kbp genome with two insertion sequences.…”
Section: Sequence Analysismentioning
confidence: 99%
“…16 The "Vhmllikevirus" phages VHML, VP58.5, and vB_VpaM_MAR have similar genome sizes to ϕH111-1 (41-43 kbp) but are thought to lysogenize as linear plasmids with telomeres in Vibrio species. [17][18][19] The commonalities among ϕH111-1, AcaML1, and the "Vhmllikevirus" phages are largely restricted to the morphogenesis genes. These phages all have P2-like tail proteins, but encode capsid morphogenesis/DNA packaging and accessory proteins that are unrelated to those of P2 ( Table 2).…”
Section: Sequence Analysismentioning
confidence: 99%
“…Apart from 'a prototype' -the enterobacteria phage N15, which was isolated in 1964 -only six other phages are known to lysogenize their hosts as linear telomere plasmids (Ravin, 2015). They are the siphoviruses FKO2 of Klebsiella oxytoca (Casjens et al, 2004) and PY54 of Yersinia enterocolitica (Hertwig et al, 2003), and the myoviruses of marine bacteria: VP882, Vp58.5 and vB_VpaM_-MAR of Vibrio parahaemolyticus (Lan et al, 2009;Zabala et al, 2009;Alanis Villa et al, 2012), and FHAP-1 of Halomonas aquamarina (Mobberley et al, 2008). All of them encode a hallmark protein called protelomerase, along with plasmid partitioning proteins ParA and ParB, required for this type of lysogeny.…”
Section: Introductionmentioning
confidence: 99%
“…All of them encode a hallmark protein called protelomerase, along with plasmid partitioning proteins ParA and ParB, required for this type of lysogeny. Another myovirus, VHML of Vibrio harveyi (Oakey et al, 2002) that is closely related to one of the abovementioned phages, VP58.5 (Zabala et al, 2009) also contains genes encoding homologues of the N15-like protelomerase (Ravin, 2015) and partitioning protein ParA (Oakey et al, 2002). VHML was initially described as a prophage integrated into the host chromosome (Oakey et al, 2002), but later it was suggested that it may be a linear plasmid-like prophage as well (Lima-Mendez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…All of them were identified in γ-proteobacteria, and they fall into two groups: the siphoviruses ϕKO2 of Klebsiella oxytoca (15) and PY54 of Yersinia enterocolitica (16), and the myoviruses of marine bacteria: phages VP882, Vp58.5, and vB_VpaM_MAR of Vibrio parahaemolyticus (17)(18)(19) and phage ΦHAP-1 of Halomonas aquamarina (20). All of them are related to N15 and carry a similar genetic determinants responsible for prophage replication and generation of covalently closed telomeres.…”
Section: The Family Of Linear N15-like Phage-plasmidsmentioning
confidence: 99%